The Influence of Psychological Capital on Performance and Work Engagement Mediated by Job Satisfaction in Nurses at Pertamedika Ummi Rosnati Hospital, Banda Aceh City - Muhammad Farhan Lubis; Ade Irma Suryani; Lenny Rakhmawati (Westscience Press, 2025)
This research aims to examine the effect of psychological capital on performance and work engagement, with job satisfaction as a mediating variable, among nurses at Pertamedika Ummi Rosnati Hospital, Banda Aceh. The data were collected through a questionnaire distributed to 138 nurses, using a census sampling technique. The analysis results indicate that psychological capital significantly and positively influences both performance and work engagement. Moreover, psychological capital also has a significant and positive impact on job satisfaction. In turn, job satisfaction positively and significantly affects performance and work engagement. Furthermore, job satisfaction serves as a mediating variable in the relationship between psychological capital and both performance and work engagement.